Bathocuproine Buffer Layer Effect on the Performance of Inverted Perovskite Solar Cells - Touafek, Naïma; Dridi, Chahrazed; Mahamdi, Ramdane (Journal of Technology Innovations in Renewable Energy, 2020)
To boosting the performance of inverted p-i-n-type planar hetero-junction architecture photovoltaic cells based on CH3NH3PbI3 perovskite materials, a thin buffer layer Bathocuproine (BCP) is introduced between the Electron Transporting Layer (ETL) PCBM and the metal contact. The trends in parameters Perovskite Solar Cells (PSCs) inserting BCP is studied using solar cell capacitance simulator (SCAPS-1D). The obtained results of optimizing the thickness of the Bathocuproine (BCP) buffer layer exhibited optimum value at 5 nm, with power conversion efficiency (PCE) of 17.30 %, VOC of 1.39 V, and FF of 62.89 %. The carrier concentration was higher than 1017 cm-3 increases sharply the conversion efficiency by about 0.35-2.3 %. Further, the lower metal work function (Фm<4.3 eV) enhances the electrical parameters where the efficiency up to 21.3 %. Keywords: Solar cell, Perovskite, CH3NH3PbI3, BCP, SCAPS, Metal Work Function.